Identities and Migrations: a Borderless Middle East’s Perspective - Lorenzo Kamel (Storicamente, 2015)
New sources have been recently released fostering the thesis according to which a significant percentage of the Palestinian Arabs were originally immigrants from Egypt and other neighbouring countries. Their histories, as highlighted by some scholars, are largely unknown and continue to be ignored. This article aims to shed light on these aspects, assessing them from a borderless Middle East’s perspective. The aim is to show the process through which a local complex reality has been simplified and denied in its continuity.